Síntomas depresivos y consumo de tabaco en estudiantes de Bachillerato del colegio Manuel Ignacio Monteros Valdivieso de Loja - Paute Torres, Abigail Alexandra (2023)
Depressive symptoms and tobacco consumption are currently considered silent but frequent health problems, with aggravating consequences. The aim of this study was to determine depressive symptoms and tobacco consumption according to age group and sex, establishing their correlation in high school students of the Manuel Ignacio Monteros Valdivieso school in Loja. It was a quantitative, cross-sectional study, with a sample of 141 participants in which the Patient Health Questionnaires PHQ -2 and PHQ -9 and the Questionnaire for the classification of cigarette consumers (C4) for young people were applied. In the study, it was observed that 70% (n=98) of the individuals presented mild to severe depressive symptoms, mainly between 19 to 23 years old, with no significant difference between male and female sex; in relation to tobacco consumption, it was shown that 32% (n=46) of the population studied consumed tobacco, this risk was higher in students between the ages of 14 to 18 years belonging to the male sex. Likewise, it was observed that 68% (n=95) showed to be practically null with respect to tobacco consumption with no difference between the age intervals, but prevailed by the female sex. Concluding with the results obtained indicate that there is an influence of depressive symptoms on cigarette consumption. The findings highlight the difference between age and gender for suffering from depressive symptoms and tobacco consumption